The impact of strength training on the prevention of orthopedic injuries in sports: a literature review. - Julia Szewczyk; Michał Świta; Anna Szuciak (Nicolaus Copernicus University in Toruń, 2024)
Introduction: The perception of physical activity has evolved, influenced by urbanization, media, and public health initiatives. While regular physical activity offers health benefits, musculoskeletal injuries in athletes remain a concern, often going unnoticed due to subtle symptoms. Preventing these injuries is crucial, with strength training (ST) emerging as a strategy to enhance stability and reduce injury risk. Purpose of the Study: This review examines the impact of strength training on preventing orthopedic injuries in athletes, focusing on mechanisms like muscle strengthening, joint stabilization, improved endurance, and correcting imbalances. It evaluates research on ST's effectiveness in preventing knee, ankle, hip, back, and upper limb injuries. Methodology: A comprehensive search of databases, including PubMed, Scopus, and Google Scholar, was conducted using keywords such as "strength training," "orthopedic injury prevention," "musculoskeletal stability," "injury risk reduction," and "sports injuries." Results: Strength training plays a key role in preventing sports injuries by enhancing muscle strength, joint stability, and endurance, addressing musculoskeletal weaknesses and imbalances. Studies show ST significantly reduces knee, ankle, hip, and back injuries. For instance, knee injuries are prevented by strengthening the hip abductors and quadriceps, while ankle injuries are mitigated by improving core and lower limb strength. ST also prevents injuries in "overhead sports" by enhancing shoulder stability. Keywords: strength training, orthopedic injury prevention, musculoskeletal stability, sports injuries, injury risk reduction.